(untitled) (GYMNASIUM, 2017)
Over the years attitudes and believes about what is the role of parents in occupational therapy intervention has been changed. Family-centered occupational therapy is approach that is based on the believes, values and preferences of each family as a unit. Working with families is always context related and the aim is to empower the family system. Purpose. Is to find out if there is connection between the principles of family centered occupational therapy and the competences for occupational therapist. Method. Analyzing the concepts connected with family centered occupational therapy and competences in practice according to literature. Comparing the information in order to identify the possible gaps and similarities. Results. The concept of family-centered is wildly used, but it is more connected with client’s needs than to focused on the dynamic and quality of life of family as a system. Competences for occupational therapy shouldn’t only be focused on needs of individuals and groups.